Integrated business process management in contemporary enterprises: A challenge or a necessity? - Stanisław Brzeziński; Agnieszka Bitkowska (Contemporary Economics, 2022)
The progressing globalization processes and new technological solutions require the organization to constantly adapt to changes taking place in the environment. More and more companies implement process management, both at the strategic and operational levels, considering the project and knowledge perspective. The article aims to show the usefulness of building the concept of integrated process management, based on the triad: processes, projects, knowledge in modern enterprises. The following research methods and techniques were used in the article: analysis of the literature on the subject, comparative analysis of the results of research carried out in the world, and the effects of own research carried out in Poland. The research has shown that usefulness of integrated business process management is ensured by the coordination of processes and links with strategic and operational assumptions, synergies of processes, projects, and knowledge. Such a solution can help the organization and transformation processes in the effective implementation of the strategy.
Keywords: L22; O31; M19; 330; business process management; projects; knowledge; integrated business process management